Characterization of the atmospheric turbulence at the Sutherland site and conceptual design study and optimization of an Adaptive Optics system for the Southern African Large Telescope - Catala, Laure (Department of Astronomy, 2017)
To support the potential development of an AO system for SALT, a site monitoring campaign of the Sutherland site was initiated in 2010. This campaign also led to the participation in the development of a new instrument to characterize the atmospheric turbulence. The results from five years of site testing were used in AO simulations in order to demonstrate the potential capabilities of an AO system on SALT. The site testing study produced up-to-date seeing values and provided a measurement of the atmospheric turbulence profiles. I found a median seeing value of 1.51". The main contributor to the turbulence is clearly the ground layer, below 1 km, responsible for 83% of the turbulence. The next most significant contributor is the wind shear layer around 3 km. Seasonal trends show that slightly worse seeing conditions occur during the winter months due to predominant East, South-easterly winds that are associated with degraded seeing conditions. In addition to the main site testing campaign, I helped develop the "Profileur de Bord Lunaire" (PBL, Profiler of Moon limb in English), a new instrument that uses the Moon limb to measure the atmospheric turbulence profile. The work on the data processing and inversion method led to the extraction of high altitude-resolution profiles of the turbulence strength. I present here those results along with a comparison with profiles obtained with the Multi-Aperture Scintillation Sensor (MASS). Using the results from the site testing campaign along with the SALT optical design, I simulated the general dimensioning of a system for SALT that would use a single natural guide star (NGS). The trade-off between performances and sky coverage resulted in a 34x34 system using NGS in the range 10 to 14 magnitude in R-band. The 34x34 dimensions refer to the number of subapertures of the Shack-Hartmann wavefront sensor. I conclude with the significant improvement in spectroscopic performance for SALT that could be achieved by implementing an AO system. The gains in encircled/enslited energy are most significant in the near infrared where gains of 183% could be achieved at 1600 nm for the planned Near-infrared upgrade to the Robert Stobie Spectrograph (RSS). The gains in enslited and encircled energy at 700 nm for the visible arm of RSS and the High-Resolution Spectrograph (HRS) are limited to a maximum of 22% and 34%, respectively, due to the large apertures adapted to seeing-limited observations. Further gains could be achieved by designing the next generation of SALT instrumentation to take full advantage of an AO system.